Exploring the potential of assessment efficacy in sports coaching - A Response to Commentaries - Hay, P.; Dickens, S.; Crudgington, B.; Engstrom, C. (International Journal of Sports Science and Coaching, 2012)
We believe that efficacious assessment practices have much to offer the field of sports coaching in terms of coach learning and the practice of coaching itself. The implementation of assessment needs to be theoretically grounded and supported by robust research initiatives. We argue that assessment can be a supportive experience, especially for those coaches for whom engagement in sport is not vocational and who would value feedback on their approach. This is important to promote safe and generative practices at the community and youth sport level, but also provides sporting organisations with the opportunities to recognise prevailing misconceptions and poor practices in coaching that get perpetuated through ill-advised engagement.